Role of Erythromycin-Regulated Histone Deacetylase-2 in Benign Tracheal Stenosis - Zhenjie Huang; Peng Wei; Luoman Gan; Tonghua Zeng; Caicheng Qin; Guangnan Liu (Canadian Respiratory Journal)
Objective. This study aims to explore the role of erythromycin-regulated histone deacetylase-2 in benign tracheal stenosis. Methods. The rabbit model of tracheal stenosis was established. The rabbits were randomly divided into 8 groups. Histone deacetylase-2 (HDAC2) expression was detected by immunofluorescence. The expression of type I collagen and type III collagen was detected by immunohistochemical method. The expression of TGF-β1, VEGF and IL-8 in serum and alveolar lavage fluid was detected by ELISA. The expression of HDAC2, TGF-β1, VEGF and IL-8 in bronchi of each group was detected by Western blotting method. Results. In Erythromycin (ERY) group, ERY + Budesonide group, ERY + Vorinostat group and ERY + Budesonide + Vorinostat group, the degree of bronchial stenosis was alleviated, and the mucosal epithelium was still slightly proliferated. The effect of ERY combined with other drugs was more obvious. The HDAC2 protein expression increased significantly in ERY group, ERY + Budesonide group and ERY + Budesonide + Vorinostat group and decreased significantly in Vorinostat group, the expression of collagen I and III decreased significantly in ERY group, ERY + Budesonide group and ERY + Budesonide + Vorinostat group (P<0.05). The TGF-β1, IL-8 and VEGF levels decreased significantly in ERY group, ERY + Budesonide group, ERY + Vorinostat group and ERY + Budesonide + Vorinostat group (P<0.05). Conclusions. Erythromycin inhibited inflammation and excessive proliferation of granulation tissue after tracheobronchial mucosal injury by up-regulating the expression of HDAC2, it promoted wound healing and alleviated tracheobronchial stenosis. When combined with budesonide, penicillin and other glucocorticoids and antibiotics, it had a good synergistic effect. However, vorinostat could attenuate erythromycin’s effect by down-regulating the expression of HDAC2. It may have good clinical application prospects in the treatment of tracheal stenosis.